Mobile phone use screening test: Development, validation, and implications for screening excessive mobile use - Sharma, Manoj Kumar (Ind Psychiatry J, 2020)
BACKGROUND: Early identification for the addictive use of smartphones would enable timely intervention to minimize suffering from compromised functioning and associated psychological problems. This study is the first such attempt to develop a test for addictive/excessive use of the mobile phone in the Indian context. The present study aims to develop and validate the mobile phone use screening test (MUST) for the Indian subcontinent. MATERIALS AND METHODS: Five hundred individuals aged 18–40 years, residing in the South Indian city of Bangalore participated in the study. The sociodemographic datasheet and the newly developed test were administered on these individuals to gather demographic information and patterns of excessive mobile phone use. RESULTS: The developed test has 18-items which use a self-report Likert-type scale format. The test–retest reliability was 0.93 and the Cronbach's alpha was found to be 0.86. The scoring criterion for the overall score was: <30 = mild use; 31–49 = moderate use; and 50 and above = excessive/addictive smartphone use. The scale has four components: craving, loss of control, coping, and consequences. CONCLUSIONS: The MUST can be used for the identification of addictive/excessive use of mobile phone among adolescents and young adult groups.